The Influnce Of Brand Equity Dimensions On Use E-Wallet DANA With E-Trust As Intervening Variable - Beltasari, Ruri Acnes; Santoso, Adi; Sumarsono, Hadi (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2024)
The use of non-cash payments is increasingly being used by users in carrying out transactions. The concept of e-wallet is to store money in cash and non-cash transactions. This article aims to understand the level of influence of Brand Awareness, Brand Association, Brand Loyalty, and Perceived Quality on Decisions to Use Digital Money with E-Trust as an Intervening Variable for DANA Application Users. The sampling method used the Simple Random Sampling technique for 125 respondents. Data collection uses a questionnaire and uses SMART-PLS 3.0. The results of this research show that Brand Awareness does not have a positive and significant influence on e-commerce but has a positive and significant influence on user decisions. Brand Association has a significant influence on the level of trust (E-trust) but does not have a positive and significant influence on user decisions. Perceived Quality has a positive and significant influence on the level of trust (e-tsrut) and has a positive and significant influence on user decisions. Brand Loyalty has a positive and significant influence on users' decisions in using the DANA e-wallet. E-commerce has a positive and significant influence on user decisions and mediates brand loyalty on user decisions on the DANA application. Keywords: Brand Awareness, Brand Association, Brand Loyalty, Perceived Quality of Use Decisions, E-Trus